Oxidative stress and inflammation in hemodialysis: a comparison of patients with or without advanced nonalcoholic fatty liver disease (NAFLD) - Vanja Kalacun; Robert Ekart; Sebastjan Bevc; Pavel Skok; Radovan Hojs; Nina Vodošek Hojs (Renal Failure)
Nonalcoholic fatty liver disease (NAFLD) and chronic kidney disease are global public health issues associated with high morbidity and mortality. Both diseases are also interlinked. Little is known about the meaning of NAFLD in hemodialysis (HD) patients. Therefore, the aim of our study was to investigate the difference in oxidative stress and inflammation in HD patients with or without advanced NAFLD. Seventy-seven HD patients were included (65.14 ± 12.34 years, 59.2% male) and divided according to abdominal ultrasound and two-dimensional shear wave elastography (2D-SWE) measurements into two groups: 1) no NAFLD or no advanced NAFLD (2D-SWE <9 kPa) and 2) advanced NAFLD (2D-SWE ≥9 kPa). Medical history data and blood results were collected. HD patients with advanced NAFLD had significantly higher levels of 8-hydroxy-2’-deoxyguanosine (8-OHdG; p = 0.025), tumor necrosis factor-alpha (TNF-α; p = 0.023), and intercellular adhesion molecule 1 (ICAM-1; p = 0.015) in comparison to HD patients without advanced NAFLD. Interleukin 6 (IL-6) was higher in the advanced NAFLD group, but the difference was of borderline significance (p = 0.054). There was no significant difference in high-sensitivity C-reactive protein (hs-CRP), and vascular cell adhesion molecule 1 (VCAM-1) between groups. In binary logistic regression analysis, advanced NAFLD was significantly associated with 8-OHdG and ICAM-1. In conclusion, higher oxidative stress and inflammation levels are present in HD patients with advanced NAFLD.